Developing a piggyBac Transposon System and Compatible Selection Markers for Insertional Mutagenesis and Genome Engineering in Yarrowia lipolytica. Issue 5 (25th March 2018) - Wagner, James M.; Williams, Eden V.; Alper, Hal S.
Abstract : Yarrowia lipolytica is a non‐conventional yeast of interest to the biotechnology industry. However, the physiology, metabolism, and genetic regulation of Y. lipolytica diverge significantly from more well‐studied and characterized yeasts such as Saccharomyces cerevisiae . To develop additional genetic tools for this industrially relevant host, the piggyBac transposon system to enable efficient generation of genome‐wide insertional mutagenesis libraries and introduction of scarless, footprint‐free genomic modifications in Y. lipolytica . Specifically, we demonstrate piggyBac transposition in Y. lipolytica, and then use the approach to screen transposon insertion libraries for rapid isolation of mutations that confer altered canavanine resistance, pigment formation, and neutral lipid accumulation. We also develop a variety of piggyBac compatible selection markers for footprint‐free genome engineering, including a novel dominant marker cassette ( Escherichia coli guaB ) for effective Y. lipolytica selection using mycophenolic acid. We utilize these marker cassettes to construct a piggyBac vector set that allows for auxotrophic selection (uracil or tryptophan biosynthesis) or dominant selection (hygromycin, nourseothricin, chlorimuron ethyl, or mycophenolic acid resistance) and subsequent marker excision. These new genetic tools and techniques will help to facilitate and accelerate the engineering of Y. lipolytica strains for efficient and sustainable production of a wide variety of small molecules and proteins. Abstract : The piggyBac transposon system enables genome‐wide insertional mutagenesis and scarless, footprint‐free genomic editing in the oleaginous yeast Yarrowia lipolytica . piggyBac compatible selection markers have been developed for genomic integration via auxotrophic selection (uracil or tryptophan biosynthesis) or dominant selection (hygromycin, nourseothricin, chlorimuron ethyl, or mycophenolic acid resistance). After integration, marker cassettes can be precisely excised from the Y. lipolytica genome using a mutant 'excision‐only' piggyBac transposase.